The Influence Of Preconceptional Nutrition Counseling On Knowledge And Attitude Of Women Of Reproductive Age - Devi Lukiana; Titin Eka Sugiatini (Lembaga Pengembangan Kinerja Dosen, 2022)
Background : Health problems in the preconception period include anemia, obesity and chronic lack of energy. In Indonesia, cases of Chronic Energy Deficiency are caused by lack of nutritional intake such as energy and protein, so that the nutrients needed by the body are not fulfilled. To prevent the risk of Chronic Energy Deficiency in pregnant women before pregnancy, women of childbearing age must have good nutrition. Maternal nutritional status before pregnancy has a significant influence on the incidence of LBW. Knowledge of nutrition plays an important role in fulfilling one's nutritional adequacy. The level of knowledge will encourage a person to have optimal abilities in the form of knowledge and attitudes. Objective : Knowing the effect of preconception nutrition counseling on the knowledge and attitudes of women of childbearing age. Methods : Quasi experimental with one group pretest-posttest design. The sample in this study was some women of childbearing age who were married in the preconception period from July to September 2022 in Sanggar Buana Village, Seputih Banyak District, Central Lampung as many as 81 people, the sampling technique was purposive sampling. Results : Most of them have knowledge of WUS before being given counseling that is enough 64.2% and after 85.2% have good knowledge. Attitudes before being given counseling were mostly negative 55.6% and afterward were positive 97.5%. There is an effect of preconception nutrition counseling on the knowledge and attitudes of women of childbearing age (p value 0.000). Conclusions and Suggestions: There is an effect of preconception nutrition counseling on the knowledge and attitudes of women of childbearing age. Health services are expected to provide education and counseling, especially regarding preconception nutrition